An analysis of the roots of modern Chinese Labour Law with particular reference to the PRC Labour Law 1994 - crossing the river by feeling the stones - Wu, Yixuan (2020)
This thesis tells the birth of China's modern labour law system by restoring the legislative process of the Chinese Labour Law in 1994. As a part of the legal system reform, the birth of the Labour Law was also following the guiding strategy, ‘Crossing the River by Feeling the Stones’, of the Chinese macro institutional reform. This thesis attempts to solve two questions. What are the ‘stones’ in the river? How those stones have paved the way or direction? In order to answer these questions, this article combs and studies China's reform and adjustment of the labour system and legislative work from the end of the 1970s to 1994. At the same time, in order to restore the process and supplement the information, this article collects and sorts out the memories of some legislators. Through interviews with those who have experienced the legislative process, this thesis discovered the main controversial issues in the legislative process, which was also the original design of this law. There are three main innovations in this thesis: First, this article reveals the main factors (the stones) considered by the legislator in the process of labour law legislation; Second, this article discovered the holistic discussion of drafting process of labour law might not be able to provide insightful picture of how the river has been crossed. Indeed, there were at last four set of branches (components) of the river (Labour Law), which need to be crossed (to be formed) and therefore to be reviewed separately. Third, the same type of stones in different branches actually played different roles in deciding the directions. In the end of the day, the river of Labour Law was crossed with hybrid nature, where not only the stones but also the branches have their joint influence that shall not be oversimplified or overlooked. The conclusion restores the trajectory of river crossing process during the birth of the modern Chinese labour law system. A number of topics attracted attention during the research process and clearly call for further ...